Experiencing art a multiple case study on the interior design of selected interactive museums in Metro Manila - Verzola, Madeleine Danielle M.; Mayo, Adelaida V. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This research made an attempt to assess the interior design of selected interactive museums in Metro Manila based on what experiences they provide to the visitors. This study also attempted to spur awareness on how Interior Design works with Museology. This study, which used a multiple case study approach, is conducted in two purposively selected interactive museums- namely Art In Island and Quezon City Experience Museum. A representative from each museum was interviewed to share their knowledge about the museum. Three conveniently chosen respondents were accompanied by the researcher to visit the museums. Observation and interview guides were used to document the design features of each museum and the experiences of each respondent while visiting the museum. Art In Island and Quezon City Experience Museum are both divided into galleries with different themes and design. By analyzing the data using the theory of Experiential Design, results showed how the interior spaces were able to create various setting that depict stories for visitors to experience themselves. On the other hand, findings show that the visitors were also brought into another dimension while enjoying the zones in Art In Island's zones and galleries in Quezon City Experience Museum, as supported by the Fourth Dimension Theory. Future studies of similar topic are recommended, exploring other museums and using other Interior Design theories.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Interactive art -- Philippines -- Metro Manila; Museums -- Philippines -- Metro Manila -- Design; Interior decoration -- Philippines -- Metro Manila